Inducinduction of Protocorm-like Bodies, Synthetic Seed Production and Cryopreservation in Phalaenopsis bellina (Rchb.f.) Christenson - Khoddamzadeh, Amir Ali (2011)
Phaleanopsis bellina (Rchb.f.) Christenson is one of the important orchid species originating from Malaysia. It is an orchid which is known to be difficult to propagate even using in-vitro techniques. This study was carried out to establish an in-vitro system for induction and proliferation of Phaleanopsis bellina. Furthermore attempt was made to convert the PLBs into synthetic seed as well as to establish a method to store the synthetic seeds both for short and long-term. An in-vitro culture procedure was established to induce protocorm-like bodies (PLBs) from leaf segments of Phalaenopsis bellina directly from epidermal cells without intervening callus on half-strength modified Murashige and Skoog (MS) medium supplemented with naphthaleneacetic acid (NAA; 0, 0.1, 1.0 mg/L) and thidiazuron (TDZ; 0, 0.1, 1.0, 3.0 mg/L). The best response was established at 3 mg/l TDZ which induced 78% of leaf segments to form a mean number of 15.5 PLBs per explant after 16 weeks of culture. No PLBs were found when leaf segments were cultured on half-strength modified MS medium supplemented with 0.1 and 1 mg/l NAA. The best induction percentage for auxin: cytokinin combination was using 1.0 mg/l NAA and 3.0 mg/l TDZ which gave 72% induction with 11 PLBs per explant. Once successfully induced, it is important to maximize the proliferation and utilization of the PLBs. In this regard, semi-solid half-strength MS and liquid Vacin and Went (VW) media with and without sucrose were used in order to find the highest survival and number of PLBs proliferation after three months in culture. Half-strength MS medium showed an average of 9 PLBs with 60% survival and mean fresh weight of 0.5g in comparison with VW medium with and without sucrose which showed an average of 4.8 and 5.3 PLBs per explant followed by 55 and 57.5% of survival respectively. Histological observations revealed that the adaxial surfaces near wounded regions had the highest number of PLBs compared to other regions of explants. Also, SEM micrographs showed that leaf derived PLB (LDP) were formed from leaf segment after 16 weeks of culture. Twelve decamer RAPD primers were used to estimate the somaclonal variation among the mother plant, the initially induced PLBs and proliferated PLBs after 3 and 6 months in culture. Eight out of twelve primers produced 172 bands with 18 polymorphic bands in all the treatments. The amplified products varied between 125 to 8000 bp. Among the primers used, P 16 produced the highest number of bands (29) while primer OPU 10 produced the lowest number (15). The range of similarity coefficient was from 0.83 to 1.0 among the different sub-cultures and mother plant. It was found that minimal or no changes occurred between the mother plant and the PLBs produced after 3 months of induction. The induced PLBs were then subcultured for six months for proliferation and this resulted in about 17% dissimilarity with mother plant. Micropropagation of Phalaenopsis bellina can be carried out successfully using ½ strength MS media for 6 months but further proliferation may result in somaclonal variation which might change the prolific characteristic of this orchid. In-vitro PLBs of Phalaenopsis bellina obtained from PLBs explants on modified semi-solid half-strength MS medium, 4-5 mm in diameter, were selected for encapsulation with different concentration of sodium alginate (3, 4 and 5%) and calcium chloride (25, 50, 75 and 100 mM) and none encapsulated PLBs as a control. PLBs encapsulated with 4% sodium alginate in 75 mM calcium chloride showed the best encapsulation combination on survival of PLBs after two weeks of incubation at 5°C giving the survival of 70 and 65%. Subsequently, PLBs encapsulated with 4% sodium alginate + 75 mM calcium chloride were used for evaluating the storage durations (15, 30, 45 and 60 days) and temperatures (5, 15, and 25°C). The highest PLBs survival of 70% was observed after 15 days storage at 5°C followed by 30 days of storage at 5°C with 50% of survival frequency. The best survival percentage in case of storage temperature for the synthetic seeds were 5°C >15°C > 25°C. The highest PLB fresh weight was 0.36g which belong to the encapsulated PLBs stored for 15 days at 5°C. In addition the lowest fresh weight of 0.19g belonged to encapsulated PLBs stored for 60 days at 25°C. The moisture content (MC) of the PLBs decreased sharply with increasing storage temperature and duration to 10.2% after 60 days at 25°C. As synthetic seeds should technically function as normal seeds, it would be useful to establish a method to store them both for short and long time. This study indicated that Phalaenopsis bellina PLBs were successfully cryopreserved by encapsulation-dehydration method. The highest re-growth of cryopreserved explants was observed when PLBs were pretreated in half-MS medium supplemented with 30 g/l sucrose for 3 days followed by preculturing on 0.75 M sucrose for 3 days. In addition, the highest sucrose concentration at 0.78 g/l was measured using HPLC in 100g of PLBs precultured on 0.75 M for 3 days. Encapsulated PLBs were dehydrated with silica gel for 6 h prior to immersion in liquid nitrogen for 1 h. Protocorm viability was tested by the 2, 3, 5-triphenyltetrazoliumchloride (TTC) assay and re-growth ability was assessed by determining the survival percentage after 2 weeks recovery. The survival rate of cryopreserved PLBs was 30% while highest viability percentage by TTC assay was 46.6%. Finally, dehydration time after freezing and thawing affected positively electrolyte leakage (EL) of the PLBs. Non-dehydrated PLBs showed the highest EL (85.3%) while the lowest amount (53%) was achieved after 6 h dehydration with silica gel.